Pursuit differential game problem with multiple players on a closed convex set with more general integral constraints - Ahmed, Idris; Kumam, Wiyada; Ibragimov, Gafurjan; Rilwan, Jewaidu (The Mathematical Association of Thailand, 2020)
In this paper, we study a pursuit differential game with many but finite number of pursuers and evaders on a closed convex subset K of Rn. Players’ motion obey ordinary differential equations and confined within the set K throughout the game. Control functions of the players are subject to general integral constraints respectively. We obtain sufficient conditions for completion of pursuit. Moreover, pursuers’ strategies that ensure completion of pursuit in a finite time are constructed.